'A Repository, a Switchboard, a Dynamo': H.L. Beales, a Historian in a Mass Media Age. Issue 3 (2nd July 2016) - Hutton, Alexander Neil
Abstract: The historian H.L. Beales (1889–1988) managed to propagate a wider interpretation of nineteenth century social history through non-academic means. Whilst Beales failed to write much in the way of history, his parallel career as an adult education tutor, radio broadcaster and editor of Pelican books meant that he acted as an important propagator of the subject. This, combined with wide influence over a considerable proportion of the younger generation, means that he should be considered as a singularly important historian of the period, who realised and adapted to the potential of new mass media to reach new audiences.